Candida tropicalis biofilms matrix - involvement on its resistance to amphotericin B - Fernandes, T. (2015)
Candida tropicalis has emerged as one of the most prevalent fungal pathogens, and its ability to form biofilms has been considered one of the most important virulence factors, since they represent high tolerance to antifungal agents. However, the mechanisms of biofilm resistance to antifungal agents remain poorly understood. Thus, the main goal of this study was to infer about the ability of amphotericin B (AMB) to control and combat C. tropicalis biofilms. Additionally, it was also intended to determine the influence of matrix components in bio- film resistance. AMB was unable to totally prevent biofilm formation and to eradicate C. tropicalis preformed biofilms. Moreover, AMB led to a significant increase of the biofilm production due to an augment of the total protein and carbohydrate contents of the matrix. The C. tropicalis biofilm matrix assumes an important role on its resistance to AMB.